Search for cyclotron absorptions from magnetars in the quiescence with XMM-Newton - Malygin, M.G.; Iakubovskyi, D.A. (Advances in Astronomy and Space Physics, 2011)
In this work, we perform the detailed analysis of absorption features in spectra of magnetar candidates observed by XMM-Newton satellite. No significant line-like feature has been found. This negative result may indicate the possible presence of smoothing out the absorption features mechanisms.